Multisite musculoskeletal pain, self-harm and suicidal behaviour in Northern Norwegian adolescents: a population-based study - Claussen, Hanna Marie Owren (UiT Norges arktiske universitet, 2020)
Background: Self-harm and suicidal behaviour commonly debuts and increases during adolescence. Suicidal behaviour is a major public health concern and is associated with later suicidal behaviour, mental health disorders and poor functioning in adulthood. Musculoskeletal pain also increases during adolescence and multisite pain is associated with increased disability and psychosocial problems. In this study, we investigate the association between adolescent multisite musculoskeletal pain and adolescent self-harm and suicidal behaviour (ASSB). Method: The Norwegian Arctic Adolescent Health Study was conducted among 10th graders (15-16-year olds) in the two northernmost counties in Norway during 2003-2005. The questionnaire was carried out in classroom settings. Univariate analyses were carried out using Chi-square tests. Logistic regression was used for the multivariable analyses examining the relationship between multisite musculoskeletal pain and ASSB. Results: A positive association was found between an increase in the number of musculoskeletal pain sites and increased suicidal intent in the dimensional range of ASSB. The association was statistically significant among adolescents reporting both suicidal ideation and self-harm after adjusting for adolescent psychosocial problems. Female adolescents reported musculoskeletal pain and ASSB to a greater extent compared to male adolescents. More male adolescents reported self-harm without suicidal ideation than female adolescents. Conclusions: The study shows that multisite musculoskeletal pain is associated with an increased suicidal intent among adolescents. Physicians should be aware of this association in order to assess and prevent suicide among adolescents with multisite musculoskeletal pain. Furthermore, awareness regarding presentation of multisite musculoskeletal pain among adolescents with anxiety and depression is warranted. Further investigations on preventative measures regarding multisite pain and ASSB particularly in female adolescents are needed.